Mitigation in turning down business proposals across cultures: the case for pragmatic competence instruction - Antoon, Gewijde Herwig De Rycker (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2014)
Writing ‘bad news’ messages in English constitute a skill critical to interpersonal effectiveness in today’s global marketplace. This study investigates the rejection (or refusal) strategies that native and non-native speakers use naturally, i.e. without the help of explicit pragmatic competence instruction. The data consist of the letters of rejection written by higher education students in response to a business proposal. These letters were analyzed in terms of four dimensions: meaning components, organizational approach and indirectness (using a framework derived from Félix-Brasdefer 2006) and the speech acts of apologizing and thanking (Wannaruk 2008). Results show that the student rejections display more variation, and even randomness, than predicted by the literature. Additionally, national culture and language appear to be much less of an explanatory factor than the students’ shared subcultural identity and exposure to similar models of communication. Overall, the data allow us to conclude that not only non-native but also native student writers would benefit from pedagogical interventions aimed at raising genre awareness and improving their intercultural pragmatic competence.